ANALISIS YURIDIS TENTANG PEMBUATAN SURAT KETERANGAN AHLI WARIS BAGI PERKAWINAN POLIGAMI OLEH PEJABAT YANG BERWENANG (Studi Kasus Putusan Pengadilan Agama Medan Nomor 314/Pdt.G/2014/PA.Mdn) - CAHAYA HASANAH (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING:1. Hasballah Thaib 2. Syahril Sofyan 3. Utary Maharany An heir cannot automatically have control over and transfer title of the inheritance to become his rights by ignoring the testator. He has to provide SKAW (notification of heir) which states who the heir is and who the testator is. An heir is a person who, at the time of his death, is kin or a bond of matrimony to a testator, a moslem, and legally becomes an heir. SKAW is one of the documents which become of the references for distributing inheritance. It is adjusted to the authority of the official who makes it and adjusted to the group of people that are affective for the Indonesian citizen. It is made underhandedly and validated by village head and subdistrict head without any scuritiny so that it becomes uncertain about the number of heirs because it is made based on Family card. The result of the research shows that there is no specifc regulation on drawing up SKAW because it is made based on the three groups. The responsibility of the official who draws it up is devided into the categories: first, according to the state administration, by revising or canceling it, secondly, when there is an indication that it harms other people, and thirdly, according to criminal act, when there is evidence that there is a forged information in the authentic certificate. The religious court has the authority to examine, decide, and settle the case of a moslem when there is a dispute in inheritance. Keywords : Letter of notification of Heirs, Polygamy, Authorized Official